Raman spectroscopy for skin cancer diagnosis and characterisation of thin supported lipid films - Larraona-Puy, Marta (2012)
Raman spectroscopy is a powerful tool in oncological imaging. Optical biopsies in which an accurate diagnosis of the tumour areas is spectroscopically performed are especially interesting for application to skin cancer treatments. In the first part of this dissertation a study on automated Raman spectral imaging allowed accurate diagnosis and delineation of the borders of a common type of skin cancer, basal cell carcinoma (BCC). Automated detection and imaging of BCC in skin sections excised during surgery was performed by combining Raman micro-spectroscopy with supervised multivariate mathematical algorithms based on linear discriminant analysis (LDA). The model allowed 90±9% sensitivity and 85±9% specificity in BCC detection. Raman spectral images based on the LDA model were created and compared with the gold-standard of the conventional histopathological diagnoses resulting in excellent agreement. Additional studies on the ability of the model in discriminating between BCC and hair follicles produced accurate diagnoses. In this thesis instrumental implementation and design of a Raman spectral imaging prototype aiming to reduce the acquisition time required to build the Raman spectral images was developed. High sensitivity variants of Raman spectroscopy such as surface enhanced Raman spectroscopy (SERS) are known to enable optical detection down to single molecules and can be applied to thin supported lipid research. The combination of SERS with a complementary topographic technique simultaneously synchronised adds to the chemical information the morphology of the sample surface. In the second part of this thesis simultaneous atomic force microscopy (AFM) and SERS characterisation of thin (≈15-20 nm) supported films of arachidic acid and cationic phospholipids on sapphire/silver substrates was successfully achieved. Supports were fabricated with nanosphere lithographic procedures and allowed enhancement of the weak Raman signals from the amphiphilic films by a maximum factor of ×10^8.